Higher education peacebuilding in conflict-affected societies: beyond the good/bad binary - Kester, Kevin; Abura, Mary; Sohn, Chaewon; Rho, Ella (International journal of comparative education and development, 2022)
PurposeThis comparative case study looks towards the diverse approaches of higher education to support peacebuilding, from policy and philosophy to pedagogical practices, in conflict-affected and post-conflict settings. The achievement of global development goals is dependent on addressing access to quality education in conflict-affected contexts, including higher education. However, in settings affected by conflict, higher education is often perceived to be a luxury, not a necessity. This study, then, explores whether and how higher education might support peace and development through the unique perspective of the “three faces” of higher education in conflict contexts.Design/methodology/approachThe paper is designed as a qualitative comparative case study. The research examines the work of university educators in two institutions in Afghanistan and Somaliland, highlighting the challenges and opportunities they face working in conflict-affected societies and their pedagogical responses to conflict. Data for the research were collected through in-depth interviews, documents, and digital artifacts with 12 university educators across the two institutions. The faculty teach a wide variety of subjects in the social sciences and humanities, subjects including and in addition to those specific to peace and development studies. To strengthen the interpretation of data, multiple coders were involved and intercoder reliability was conducted.FindingsFindings indicate a number of challenges and opportunities that university lecturers and their institutions face in teaching for peace in conflict-affected contexts, particularly as it relates to the “three faces” of higher education to support, impede, or reveal the complicated nuances of peacebuilding in conflict settings. Member-checking was employed with participants to enhance the reliability of the analysis.Originality/valueIn the end, the paper contributes new empirical insights into higher education in conflict-affected contexts, particularly from the standpoint of faculty. Critical perspectives and implications for curriculum, pedagogy and research are offered.